Endothelial Nitric Oxide Synthase Genotype and Ischemic Heart Disease: Meta-Analysis of 26 Studies Involving 23028 Subjects - Casas, Juan P.; Bautista, Leonelo E.; Humphries, Steve E.; Hingorani, Aroon D. (Circulation (New York, N.Y.), 2004)
Background— Polymorphisms in the endothelial nitric oxide synthase (eNOS) gene may influence the risk of ischemic heart disease (IHD), but data from published studies with individually low statistical power are conflicting. To evaluate the role of polymorphisms in the eNOS gene in IHD, we considered all available studies in a meta-analysis. Methods and Results— Case-control studies evaluating the association between the Glu298Asp, −786T>C, and intron-4 polymorphisms and IHD were searched in MEDLINE and EMBASE up to January 2003. The principal prior hypothesis was that homozygosity for eNOS Asp298, the −786C allele in the promoter, or the intron-4 ( a allele) would be associated with an increased risk of IHD. Data were available for 9867 cases and 13 161 controls from 26 studies. Homozygosity for the Asp298 was associated with an increased risk of IHD (OR, 1.31; 95% CI, 1.13 to 1.51). Although there was significant heterogeneity among studies of Asp298 ( P Het =0.0002), which was largely accounted for by a single study, the increase in risk was still significant after exclusion of that study from analysis. Homozygosity for the intron-4 a allele was also significantly associated with higher risk of IHD (OR, 1.34; 95% CI, 1.03 to 1.75). However, no significant association was found with the −786C allele (OR, 1.06; 95% CI, 0.89, 1.25). Conclusions— Individuals homozygous for the Asp298 and intron-4 a alleles of eNOS are at moderately increased risk of IHD. These findings support the proposal that common genetic variations in the eNOS gene contribute to atherosclerosis susceptibility, presumably by effects on endothelial NO availability.